Fakultas Tarbiyah dan Ilmu Keguruan Mengajar: Menginspirasi Generasi Muda untuk Cinta Bahasa Arab - Aniati, Ira; Suci Meliani; Hurriyatus Sa’adiyah (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2024)
The issue of low student interest in learning Arabic is still prevalent in elementary schools today, particularly among students at MDTA Nurul Iman Sihitang. To address this, the Faculty of Tarbiyah and Teacher Training at UIN SYAHADA Padangsidimpuan launched the "FTIK Mengajar" program, which employs various strategies to enhance Arabic language learning. This program was implemented at MDTA Nurul Iman Sihitang in Padangsidimpuan Tenggara. The objective of this community service is to increase the interest in learning Arabic among 41 students at MDTA Nurul Iman during the 2022/2023 academic year. The program utilized a direct mentoring method for teaching Arabic. Data were collected through observation, interviews, and documentation, and then categorized into four stages: planning, action, observation, and analysis of student attendance and activities. As a result, the students' interest in learning Arabic showed a significant improvement, contributing to their overall success in both worldly and spiritual aspects. Di sekolah dasar saat ini, masih ada masalah minat siswa dalam belajar bahasa Arab, terutama di MDTA Nurul Iman Sihitang. Untuk mengatasi masalah ini, Tarbiyah dan Ilmu Keguruan UIN SYAHADA Padangsidimpuan meluncurkan program "FTIK Mengajar" di MDTA Nurul Iman Sihitang di Padangsidimpuan Tenggara . Program ini menggunakan berbagai pendekatan untuk meningkatkan pembelajaran bahasa Arab. Tujuan pengabdian kepada masyarakat ini adalah untuk mendorong  siswa MDTA Nurul Iman untuk belajar bahasa Arab pada tahun akademik 2022/2023. Pengabdian ini menggunakan pendekatan pendampingan langsung untuk mengajar bahasa Arab. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Setelah dikumpulkan, data dibagi menjadi empat tahap: perencanaan, tindakan, observasi, dan analisis kehadiran serta aktivitas siswa. Hasilnya, minat siswa dalam belajar bahasa Arab meningkat.